SEJARAH KONFLIK UMMAT ISLAM DI INDONESIA - Zainurofiq Zainurofiq (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
In the course of history, there are at least three problems that have induced conflicts among Muslim ummat in Indonesia. First, an ideological conflict that divides Muslims into those who aspires Islam as a basis of the state and those who promote nationalism as a principal basis of the state. Such a conflict has occurred in the 20th century and remains take place presently. Pancasila that has been issued as an ideology of the state is not more that just a compromised, middle-road solution to this conflict. Second, a conflict of religious thought that has embodied in the Islamic organizations. Formerly, this can take forms of ‘traditionalist’ and ‘reformist’ conflict that is represented respectively by Nahdlatul Ulama and Muhammadiyah, or even a conflict of intra-reformist organizations such as Muhammadiyah-Serikat Islam, or a conflict of intra-single organization as happens to NU. The emergence of new Islamic mass-organizations in the Reform era seems to be a valve of this conflict of religious thought. Third is a conflict of the nature and orientation of Indonesian culture. In the early 1930s, a sharp conflict revolving around whether Indonesian culture should emulate the Western culture or Eastern culture took place. The debate over Pornography Act currently is not other than a sort of this conflict.